2008
DOI: 10.1099/ijs.0.65489-0
|View full text |Cite
|
Sign up to set email alerts
|

Rheinheimera soli sp. nov., a gammaproteobacterium isolated from soil in Korea

Abstract: A Gram-negative, non-spore-forming bacterium, designated strain BD-d46 T , was isolated from a playground soil sample in Jinju, South Korea. Cells were straight or curved rods and showed catalase-and oxidase-positive reactions. Growth of strain T was observed between 15and 35 6C (optimum 25-30 6C) and between pH 6.5 and 8.0 (optimum pH 7.0-7.5). The predominant fatty acids were summed feature 3 (C 16 : 1 v7c and/or iso-C 15 : 0 2-OH), C 12 : 0 3-OH and C 16 : 0 . Strain BD-d46 T contained phosphatidylethanola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 18 publications
1
32
1
Order By: Relevance
“…The DNA G+C content of the type strain is 47 mol% (T m ). The polar lipids consist of phosphatidylglycerol, phosphatidylethanolamine, two unknown phospholipids Romanenko et al (2003), Yoon et al (2007), Halpern et al (2007), Zhang et al (2008), Brettar et al (2002Brettar et al ( , 2006, Merchant et al (2007), Ryu et al (2008), Chen et al (2010), Li et al (2011), Fonnesbech Vogel et al (2000, Roh et al (2009) and Kim et al (2009Kim et al ( , 2010 unless indicated. All strains are positive for catalase and oxidase activities, hydrolysis of gelatin, starch and Tween 80 and API ZYM tests for alkaline phosphatase and leucine arylamidase; all strains are negative for hydrolysis of L-arginine, indole production, fermentation of D-glucose, assimilation of mannose, gluconate, caprate, adipate and phenylacetate and API ZYM tests for lipase (C14), b-galactosidase, b-glucuronidase, a-mannosidase and a-fucosidase.…”
Section: Emended Description Of the Genus Rheinheimera Brettar Et Almentioning
confidence: 99%
“…The DNA G+C content of the type strain is 47 mol% (T m ). The polar lipids consist of phosphatidylglycerol, phosphatidylethanolamine, two unknown phospholipids Romanenko et al (2003), Yoon et al (2007), Halpern et al (2007), Zhang et al (2008), Brettar et al (2002Brettar et al ( , 2006, Merchant et al (2007), Ryu et al (2008), Chen et al (2010), Li et al (2011), Fonnesbech Vogel et al (2000, Roh et al (2009) and Kim et al (2009Kim et al ( , 2010 unless indicated. All strains are positive for catalase and oxidase activities, hydrolysis of gelatin, starch and Tween 80 and API ZYM tests for alkaline phosphatase and leucine arylamidase; all strains are negative for hydrolysis of L-arginine, indole production, fermentation of D-glucose, assimilation of mannose, gluconate, caprate, adipate and phenylacetate and API ZYM tests for lipase (C14), b-galactosidase, b-glucuronidase, a-mannosidase and a-fucosidase.…”
Section: Emended Description Of the Genus Rheinheimera Brettar Et Almentioning
confidence: 99%
“…T was ubiquinone-8 (Q-8), in line with that of species of the genus Rheinheimera whose isoprenoid quinones have been described (Yoon et al, 2007a;Ryu et al, 2008;Li et al, 2011;Liu et al, 2012;Chen et al, 2013;Zhong et al, 2014). The cellular fatty acid profiles of strain J-MS1…”
Section: Cell Biomass Of Strain J-ms1mentioning
confidence: 86%
“…At the time of writing, the genus comprises 15 species with validly published names (http://www.bacterio.net/ rheinheimera.html; Euzéby, 1997), including three recently described species of the genus Rheinheimera, Rheinheimera tuosuensis (Zhong et al, 2014) and Rheinheimera hassiensis and Rheinheimera muenzenbergensis (Suarez et al, 2014). The earliest described members of the genus Rheinheimera were of marine origins, but those described recently have been isolated from a variety of environments, including seawater, chironomid egg mass, soil, roots of fresh rice plants, a freshwater culture pond, marine sediments and a slightly alkaline lake (Brettar et al, 2002(Brettar et al, , 2006Romanenko et al, 2003;Halpern et al, 2007;Merchant et al, 2007;Yoon et al, 2007a;Ryu et al, 2008;Zhang et al, 2008;Chen et al, 2010Chen et al, , 2011Li et al, 2011;Liu et al, 2012). In this study, a novel bacterial strain, designated J-MS1 T , which was isolated from seashore sand on the South Sea in South Korea and showed dark brown colonies, is described.…”
mentioning
confidence: 99%
“…Strains KMM 9512 and KMM 9513 T contained Q-8 as the major ubiquinone that is consistent with that obtained for most Rheinheimera species (Yoon et al 2007;Liu et al 2012;Chen et al 2013;Zhong et al 2014). It has been reported in addition to the presence of Q-8 as predominated component bacteria of R. soli (Ryu et al 2008) and R. nanhaiensis (Li et al 2011) contained MK-7 (25 %) and Q-7 (2 %), respectively. The polar lipid composition of strains KMM 9512 and KMM 9513 T and related Rheinheimera type bacteria was found to be similar and included phosphatidylserine, phosphatidylglycerol, phosphatidylethanolamine, unknown aminophospholipids, unknown aminolipids (excepting R. nanhaiensis KACC 14030 T which did not contain aminolipids), unknown phospholipids, and unknown lipids (Supplementary figure S1).…”
Section: Morphological and Physiological Characterizationmentioning
confidence: 94%
“…Members of the genus Rheinheimera are ubiquitous microorganisms, which have been isolated from a broad range of natural habitats including surface and deep seawater (Brettar et al 2002(Brettar et al , 2006Romanenko et al 2003;Yoon et al 2007), marine sediments (Li et al 2011), estuarine and freshwater (Merchant et al 2007;Chen et al 2010bChen et al , 2013, saline and slightly alkaline lakes (Zhong et al 2014;Liu et al 2012), soil (Ryu et al 2008), rhizosphere and roots of plants (Suarez et al 2014;Zhang et al 2008), and chirinomid egg mass (Halpern et al 2007).…”
Section: Introductionmentioning
confidence: 99%